An evaluation of a methadone treatment programme : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Clark, Jahna (Massey University, 1987)
The evaluation of a methadone treatment programme was the main focus of this study. A posttest-only design, with a nonequivalent comparison group was used to evaluate both summative and formative aspects of the programme. Participants were 21 opiate abusers (methadone group) and 22 alcohol and polydrug abusers (alcohol and polydrug group) who completed a questionnaire designed to assess demographic and treatment variables, alcohol and drug usage, employment, criminal activity, health, and interpersonal relationships, in the before, during, and after treatment periods. The outcome measures revealed that the methadone programme was effective in reducing opiate, nonopiate analgesic, tranquillizer and stimulant use; decreasing high alcohol consumption to a level considered nonabusive, and decreasing the number of marijuana related criminal convictions. Unanticipated findings were a deterioration in rating of health and no change in the number of days spent sick in bed, friendship satisfaction, or number of friends out of the drug scene. No predictors of treatment outcomes were established, and there were no major differences between the methadone group, and the alcohol and polydrug group in terms of treatment effects. Recommendations for the methadone programme included detailed and procedural steps of how to cope when withdrawing from methadone treatment; health and nutrition education; and social skills and assertiveness training. These are considered essential if the philosophy and goals of the programme are to be attained.
Keywords: New Zealand; Methadone maintenance; Evaluation; Drug abuse; Treatment